Pendampingan Pendidikan Teknik Desain Berkualitas bagi Ibu-Ibu Penjahit sebagai Implementasi Sustainable Development Goals - Satyanegara, Teresa Samantha; Tjioe, Vincentia Jennifer Evelyn; Sitepu, Sri Nathasya Br (Universitas Nusantara PGRI Kediri, 2024)
Glagaharum Village Tailors have the ability to sew clothes to generate additional family income. Mother tailors have not succeeded in getting maximum income from the sewing business. The problem of mother tailors is the lack of knowledge and skills in clothing design. The purpose of providing quality design engineering education assistance for mother tailors as an implementation of the Sustainable Development Goals (SDGs) to improve the knowledge and skills of mother tailors for clothing design. The method used is training through four stages of activities, namely: pre-test, material, practice and post-test. The purpose of assistance is to provide knowledge and design skills and provide quality education in accordance with the goals of the SDGs. The results of educational assistance have succeeded in increasing design knowledge, design skills and the success of implementing providing quality education in accordance with the goals of the SDGs. Mother tailors receive a quality education program so that they succeed in making clothes according to the trending clothing designs in 2024. Mother tailors produce clothes with the latest models and the neatness of the fabric stitches has also increased.